(3fRgI GdfGXQ aj JUMjM CUhd GHf GdTGWQs - (3TgGH GdOjf CMeO Hf EHQGgje Hf Ndjd GdMdHj GdehbJ HGdLGeY GdCehj HOeTbs; (3CMeO Hf EHQGgje Hf Ndjd GdMdHj GdehbJ HGdLGeY GdCehj HOeTb, TgGH GdOjfs
(3ChdgG (B:s
(3bGd GdYHO GdabjQ GdMeO ddg GdhGMO GdbgGQ CeG HYO abO cfJ HQgI ef GdReGf YGRekG Gf GMQQ dfaSi hdSGFQ WdHI GdYde cJGH GdRjL s
(3BNQgG (B:s
(3hcd HQL eMhQ Ydi HdO hai cd HdO jeKd eWGdYg ai Gdadc GdeSJbje hdjcf gPG BNQ GdebGdI GdQGHYI hHgG fNJe GdcJGH Ef TGA Gddg s
(3GdfSNI HgG MhGTs
(3HgG LOGhd hCTcGd adcjIs
(3HgG fXGe GdJYbjHIs
(3cJHJ ai MjGI GdeDda Ch HNWg s
(3HChdgG eWGdYI hJhbjY CHj GdWGgQ eMeO Hf eMeO Hf eMeO Hf HgGOQ Gdeefi GdTGaYi SfI (B883 s
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdadcs